Obywatel Imperium czy obywatel świata? Z refleksji rzymskiej Stoi = A citizen of the Empire or a citizen of the world? Some philosophical reflections of Roman Stoics - Budzanowska-Weglenda, Dominika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Stoic doctrine was popular in the Roman Empire. It was the last period of this philosophical school but it is very important to know its history. Roman texts of the Late Stoa are sources of all Stoicism. Seneca the Younger, Roman politician, and Marcus Aurelius, Roman Emperor, are most interesting representatives of the Late Stoa. These Roman authors describe civic identity, but they refer to the Greek idea of the Cynics and Zeno of Citium, who was a founder of the Stoic school.
Keywords: stoicyzm; kosmopolityzm; Seneka, Lucjusz Anneusz (Młodszy) (retor, pisarz, filozof rzymski; ok. 4 p.n.e.-65); Antoniusz, Marek Aureliusz (cesarz rzymski; 121-180); stoicism; cosmopolitanism; Marcus Aurelius (121-180); Seneca, Lucius Annaeus (Younger) (c. 4 BC-AD 65)